The Transfer of Skills Acquired in Required English Courses to Engineering Courses: A Case Study of Students' Perceptions - Nicolas, Maureen O'Day; Nicolas, Samira (Journal of Engineering Education Transformations, 2025)
This research study investigates the transfer of acquired communication skills to engineering programs in an English in a foreign language context. The exploratory survey research investigated 77 undergraduate engineering students' perceptions of the development of their communicative skill in their second or third language as a result of two required English courses at a private Lebanese university as well as whether or not those skills were being utilized and nurtured in the engineering courses. The main finding of the study is that these students perceived that the English courses did provide opportunity for skill development in English communication. However, the findings also revealed that a lack of communication is apparent between the School of Engineering and the Department of English impeding the process of communicative skill development in English which would enhance the employability of these students as well as effectively address the ABET standard for communication.